Answer:
x = -0.2
Explanation:
Cross multiply
9* 0.2(6x + 1) = 3.6 * 0.5x Combine the coefficients on the right.
1.8 (6x + 1) = 1.8 x Remove the brackets on the left
1.8*6x + 1.8 = 1.8x Multiply the factors on the left. Don't do anything with the plus sign
10.8x + 1.8= 1.8x Subtract 1.8 from both sides
10.8x = 1.8x - 1.8 Subtract 1.8x from both sides
10.8x - 1.8x = -1.8
9x = - 1.8 Divide by 9
x = -1.8/9
x = - 0.2
Check
This is one question you should check. There's lot's of room for an error.
LHS
0.2(6x+1)/3.6
0.2(6 * -0.2 + 1) / 3.6
0.2( - 1.2 + 1) / 3.6
0.2( - 0.2) / 3.6
- 0.04 / 3.6
- 0.011111111
RHS
0.5 ( - 0.2)/9
-0.1/ 9
- 0.0111111 And the left and right side check.